The Impact of The Covid-19 Pandemic on The Economic and Psychological Condition of Individuals And Societies - Aleksandra KUZIOR; Małgorzata Mańka-Szulik; Izabela MARSZAŁEK-KOTZUR (Communications of International Proceedings, 2021)
Due to the spreading pandemic of the SARS-CoV-2 virus causing COVID-19 disease, many restrictions have been introduced in the area of everyday human life. An increase in the number of cases, which affected almost the entire globe, has resulted in bans on gatherings, restrictions on interpersonal contacts and movement, as well as the establishment of a smaller number of places that people can visit, limited to the essential ones. The economy of both large, medium and small businesses has collapsed. This new situation, manifested by the absence of opportunities to meet other people, difficulties concerning active participation in social, professional, cultural and even family life, as well as economic and existential uncertainty, has an increasingly negative influence on people and brings consequences that are difficult to predict. The following article attempts to explain some of the economic threats arising from the pandemic as well as its impact on the lives of individuals and communities.
Keywords: pandemic; crisis; restrictions; threats; isolation; effects